An investigation of high-performance team sport coaches` planning practices - Kinnerk, P.; Kearney, P. E.; Harvey, S.; Lyons, M. (Sports Coaching Review, 2023)
The aim of this study was to provide a rich description of team sport coaches` planning practices and to evaluate these practices in light of the Game-Based Approach literature and Complex Learning Theory. Twelve Gaelic football coaches operating in a high-performance setting were recruited to participate in semi-structured interviews. Coaches prepared two coaching session plans used as prompts within the interview. An iterative thematic analysis developed three major themes: (1) practice activity design, (2) sequencing of practice session content, and (3) contextual factors influencing planning. Despite strong indications of coach engagement with pedagogy in aspects of their session planning, the findings also revealed missed opportunities, with coaches failing to provide explicit learning intentions for session plans, in attention to session sequencing, and limited small-sided game designs. Given these missed opportunities, this paper illustrates how coaches can engage with research and theory to elevate the quality of their planning of coaching sessions.